Smells like teen spirit: Associations between odours and stages of life – A preliminary study. (July 2017) - Danner, Lukas; Wendelin, Martin; Buchinger, Elisabeth; Derndorfer, Eva; Majchrzak, Dorota; Maunz, Susanne; Siegmund, Barbara; Duerrschmid, Klaus
Highlights: Non-trained individuals associate selected odours with specific life stages. Liked odours are more often associated with kids and adolescents, and non-liked odours with the group of elderly persons. There is a positive correlation between the identification rates of odours and their liking. Abstract: This work investigated, whether or not non-trained individuals would assign seven selected odours from different odour groups (i.e. fruity - citrus, vanilla, floral, spicy-brown, confectionery, green and nutty ) according to the concepts of life stages (i.e. kids, adolescents, adults, elderly). Naïve participants were recruited from four different age groups: (i) kids 6–10 years of age, (ii) adolescents 11–20 years, (iii) adults 21–65 years, and (iv) seniors older than 65 years. Results show that six out of seven odours were significantly assigned to a specific life stage by the total of participants. The majority of the participants associated the odours confectionery and vanilla with the kids' group; floral and spicy - brown to the adults' group and green and nutty to the group of elderly people. No odour was clearly assigned to the adolescents' group. These assignments are largely consistent across the investigated age groups, although seniors seem to be less discriminant than the other groups. In contrast to other odours, fruity-citrus seems to be assigned differently by the different age groups. The data reveal small gender effects indicating that female test persons assigned the floral odour more often to their own age group and vanilla odour to kids more frequently compared to male participants. A positive correlation between odour identification and the liking was found, showing that odours correctly identified by the participants were liked significantly more compared to not identified odours. Furthermore, individuals who disliked a specific odour, assigned this odour more frequently to the senior age group compared to individuals liking the same odour.